Measuring Roots An updated approach - Mancuso, Stefano; Ed (springer, 2012)
Roots represent half of the plant body {u2013} and arguably the more interesting half. Despite its obvious importance for the whole plant, until recently our knowledge of the root apparatus was very limited, mostly due to the inadequacy of the techniques available. Recent advances in the visualization and measurement of roots have resulted in significant progress in our understanding of root architecture, growth and behaviour. In this book international experts highlight the most advanced techniques, both lab and field methods, and discuss them in detail. Measuring Roots combines academic and practical aspects of this topic, making it a universal handbook for all researchers and others interested in root-measuring methods.